Review of Data Provision to the Fund for Surveillance Purposes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper reviews how well members are providing the data the Fund needs, how well staff is handling issues of data inadequacy, and how the Fund's data needs are evolving. The aim is to identify possible ways of improving data provision or, where data provision can only improve as the result of protracted capacity building, to ensure that surveillance takes due account of data inadequacies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet